The politics of gating (A response to Private Security and Public Space by Manzi and Smith-Bowers) - Rowland Atkinson (European Journal of Spatial Development, 2008)
Gated residential developments, neighbourhoods to which public access is restricted, continue to generate academic, policymaker and public curiosity. Why do people want to live in these places and should public interventions be directed towards either their prevention or tacit acceptance? In a recent paper in this journal, Tony Manzi and Bill Smith-Bowers (2006) attempt to provide what they see as a more subtle approach to these developments, arguing, by way of a critique of some of my earlier work (centrally that of Atkinson and Blandy, 2005), that hostility to gated communities is misplaced on several grounds. I argue here, in return, that there are several problems with the positions they adopt, and that these should be considered if we are to effectively discuss how planning practice and housing systems should work with or against these new trends in the built environment. I argue that the key ‘problematic’ raised by gated communities is less one of empirical evidence on their impacts, since much work already points to a range of problems, and rather what these developments forecast for the character and dynamics of the urban spaces and societies we wish to live in. At the heart of my position lies a concern that either bolstering the case for gated communities or seeing them as neutral objects in the landscapes around us risks amplifying the further construction of impermeable boundaries. Critically then the risk is that ignoring the political and normative aspects of gating, as I believe Manzi and Smith-Bowers do, may lead to further and deeper socio-spatial segregation that itself excludes the voice of social groups least able to challenge or, indeed, reside in gated developments and the additional security that they appear to offer.